2010
DOI: 10.1007/s11882-010-0129-8
|View full text |Cite
|
Sign up to set email alerts
|

Are Specific Allergen Sensitivities Inherited?

Abstract: A family history of an allergic condition is a well-accepted risk factor for the development of an allergic condition in an individual, particularly for allergic disorders such as asthma, eczema, and allergic rhinitis. However, the question of whether specific allergen sensitization is inherited requires a complicated answer, as environmental exposure plays an important role in the development of allergen-specific IgE. This article summarizes the findings of recent studies in the literature regarding what is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, the question of whether specific allergen sensitization is inherited has been considered to be a complicated matter. Misiak et al 32 . reviewed the literature regarding this issue and concluded that specific allergen sensitization was influenced by both a genetic component and environmental exposure to allergen – with no clear-cut answer despite accounting for not only the complexity of allergy as a trait itself but also for the complexities of varying study methodologies as well as the evaluation of diverse populations and communities.…”
Section: Discussionmentioning
confidence: 99%
“…However, the question of whether specific allergen sensitization is inherited has been considered to be a complicated matter. Misiak et al 32 . reviewed the literature regarding this issue and concluded that specific allergen sensitization was influenced by both a genetic component and environmental exposure to allergen – with no clear-cut answer despite accounting for not only the complexity of allergy as a trait itself but also for the complexities of varying study methodologies as well as the evaluation of diverse populations and communities.…”
Section: Discussionmentioning
confidence: 99%
“…"There is a lot of conflicting evidence," says Rana Tawil Misiak, a clinician who studies allergy at the Henry Ford Health System in Detroit, Michigan, and the lead author of a recent review of allergen specificity 1 . Misiak says that the best prospect of clarification lies in studies that are large enough to include genetic variants that have been associated with different allergies.…”
Section: Allergen-specific Profilesmentioning
confidence: 99%